IMPLEMENTASI MODEL PEMBELAJARAN INTERAKTIF DALAM MATA PELAJARAN PAI UNTUK MENINGKATKAN PEMAHAMAN MULTILITERASI - Yusi Susanti; Siti Roudhotul Jannah; Dedi Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of interactive learning models in Islamic Religious Education (PAI) subjects and their contribution to improving students’ multiliteracy understanding. This research employs a qualitative approach with a descriptive method, conducted at UPT SD Negeri 01 Bengkulu. Research data were obtained through observation, interviews, and documentation techniques, and then analyzed using the theoretical frameworks of educational policy implementation, interactive learning models, and multiliteracy concepts.The findings indicate that the implementation of interactive learning models, such as Problem-Based Learning and Project-Based Learning, is able to increase students’ activeness and engagement in PAI learning. Interactive learning provides a positive contribution to the development of students’ linguistic and cultural literacy through discussion activities, group work, and the integration of PAI material with real-life contexts. However, the development of visual and digital literacy has not been optimal due to limited use of instructional media and the lack of explicit integration of multiliteracy in lesson planning and evaluation. This study concludes that interactive learning models have significant potential to enhance students’ multiliteracy understanding, but require strengthened planning, implementation, and evaluation to achieve comprehensive multiliteracy development in PAI learning.